Optimization and evaluation of machine–field parameters of remotely controlled two‐wheel paddy transplanter. Issue 6 (24th May 2022) - Lohan, Shiv Kumar; Narang, Mahesh Kumar; Javed, Mohd; Kumar, Vinay; Majumder, Atin; Raghuvirsinh, Parmar
Abstract: Amongst the various types of paddy transplanters; walk‐behind‐type transplanters are more economically viable as compared with riding‐type paddy transplanters. But, it requires more human involvement because the operator has to walk behind the two‐wheel walk‐behind‐type paddy transplanter in puddled field conditions up to about 10–22 km during a day‐long period under high temperature and humid conditions. To reduce the workload of the operator, a wireless remote‐controlled system has been developed to control the various hand control levers of walk‐behind‐type paddy transplanter through electric linear actuators and electronic control unit. The present study emphasizes the performance evaluation of the remote control system and optimizes the machine–field parameters. Response surface methodology was used with three levels of soil puddling settlement period (4, 26, and 48 h), three forward speeds (1.40, 1.85, and 2.30 km h −1 ) in two types of soils (light‐textured and medium‐textured). The response factors, that is, the effective field capacity (EFC) and field efficiency (FE) were found affected by forwarding speed, soil type, and soil puddling settlement period, but no significant effect was observed at the interaction level. The optimal value of soil puddling settlement period was 26 h at a forward speed of 2.0 km h −1 for light‐textured soil, whereas for medium‐textured soil, it was 30 h at 1.82 km h −1 . A total saving of up to 18.18% labor requirement was observed as required in the existing walk‐behind‐type paddy transplanter. The increase in EFC was observed up to 20%, resulting the net benefit per unit area and per year has been increased up to 6.59% and 15.86%, respectively. The overall results of the field evaluation showed that the remote‐controlled system for the two‐wheel paddy transplanter would be feasible at optimized field and machine parameters.